Early detection of left ventricular dysfunction in first-degree relatives of diabetic patients by myocardial deformation imaging: The role of endothelial glycocalyx damage. (15th April 2017) - Ikonomidis, Ignatios; Pavlidis, George; Lambadiari, Vaia; Kousathana, Fotini; Varoudi, Maria; Spanoudi, Filio; Maratou, Eirini; Parissis, John; Triantafyllidi, Helen; Dimitriadis, George; Lekakis, John
Abstract: Background: First-degree relatives of type-2 diabetes patients (FDR) present insulin resistance. We investigated whether FDR and dysglycaemic subjects demonstrate abnormal endothelial glycocalyx and LV deformation during postprandial hyperglycemia. Methods: We studied 40 FDR with normal oral glucose test (OGTT), 40 subjects with abnormal OGTT (dysglycaemic) and 20 subjects with normal OGTT without parental history of diabetes (normoglycaemic). At 0 and 120 min of OGTT we measured: a) LV longitudinal strain (LS) of subendocardial, mid-myocardial and subepicardial layers, global LS (GLS), peak twisting (pTw), untwisting velocity (pUtwVel), by speckle tracking echocardiography b) perfused boundary region (PBR) of the sublingual arterial microvessels; high PBR values represent reduced glycocalyx thickness. Insulin resistance was evaluated using insulin sensitivity index (ISI). Results: ISI was related with baseline PBR, GLS and pTw in all subjects (p < 0.05). Compared to normoglycaemics, FDR and dysglycaemics had higher PBR, lower ISI, GLS (− 18.4 ± 2.6 and − 16.8 ± 2.0 vs. − 19.2 ± 2.4%), subendocardial LS (− 19.0 ± 4.2 and − 17.9 ± 3.0 vs. − 20.1 ± 3.4%), pTw (14.4 ± 4.4 and 15.6 ± 6.4 vs. 16.9 ± 6.5 deg) and pUtwVel (p < 0.05 for all comparisons). A GLS < − 18% identified FDR with LV dysfunction (p = 0.016). Post-OGTT, GLS and the subendocardial LS decreased while pTw and pUtwVel increased in FDR and dysglycaemics (p < 0.05) indicating prevalence of the motion of the subepicardial over a dysfunctioning subendocardial myocardial helix. Increased PBR was related with impaired deformation markers at baseline and 120 min of OGTT (p < 0.05). Conclusion: First-degree relatives and dysglycaemics have reduced glycocalyx thickness related with impaired LV longitudinal, twisting-untwisting function. Postprandial hyperglycemia when combined with insulin resistance causes LV longitudinal dysfunction leading to increased LV twisting.